Crystalline composition and morphology in isotactic polypropylene pipe under combining effects of rotation extrusion and fibril β‐nucleating Agent. (31st October 2018) - Pi, Lin; Nie, Min; Wang, Qi
Abstract : Polypropylene (PP) pipe is extraordinarily important in modern construction and transportation engineering owing its predominant advantages over metal such as good dimensional stability, low cost, and light weight. However, low toughness and hoop strength always stand in the way of the wide application. In this study, two kinds of β‐nucleating agents (NAs) (WBG‐II and NAB‐83) were added in isotactic polypropylene and thereafter, the crystalline composition, morphology, and alignment were investigated under the combination effects of rotation extrusion and NA. The experimental results showed that both NAB‐83 and WBG‐II could promote numerous β crystals, but dot‐like NAB‐83 could only induce randomly distributed isotropic spherulites. On the contrary, by adjusting the temperature gradient along the extrusion to rotation section, WBG‐II first dissolved into PP melts and then self‐assembled into fiber‐like nuclei before the formation of PP crystals. Compared to homogeneous crystallization, fibrous WBG‐II nuclei lowered the energy barrier for PP crystals; therefore, epitaxial β lamellae grew on these fibrous NAs and stacked into β‐form hybrid shish kebabs. Meanwhile, the alignment of these highly oriented structures deflected from the axis driven by the helical movement caused by die rotation. Consequently, PP pipe with outstanding hoop tensile performance as well as excellent toughness was prepared. J. VINYL ADDIT. TECHNOL., 25:E195–E202, 2019. © 2018 Society of Plastics Engineers